Development of an E-Book for Stage Makeup Learning to Enhance Cognitive Abilities of Beauty and SPA Vocational High School Students in Phase F - Purwismaningsih , Purwismaningsih; Sutopo, Yeri; Ihsani, Ade Novi Nurul (Universitas Negeri Semarang, 2024)
This study aims to develop and analyse an e-book as a learning medium in the subject of makeup at SMK Negeri 1 Pekalongan. The focus of the research includes the feasibility, practicality, and effectiveness of the e-book used in the teaching and learning activities. The ADDIE model is employed (Analysis, Design, Development, Implementation, Evaluation), with assessment instruments from media experts, subject matter experts, teachers, and students. The results of the feasibility and validity tests show that the e-book is classified as feasible and reliable. The practicality test indicates that the e-book is considered practical by the productive teachers. Using the N-gain method, the effectiveness test shows that the e-book is quite effective in improving students' cognitive abilities and skills in stage makeup. Based on the results, the developed e-book is deemed feasible, practical, and effective for use in learning at SMK Negeri 1 Pekalongan.